KARAKTERISTIK TANAH LUNAK DI GALESONG SELATAN DENGAN STABILISASI SEMEN BERDASARKAN UJI DIRECT SHEAR - Putra Ade Kustanto; Stevy Thioritz; Hendry Tanoto Kalangi (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Atma Jaya Makassar, 2023)
This research focuses more on stabilizing the soil with additional materials. This research discusses the stabilization of soft soil originating from South Galesong using cement. The aim of this research is to determine the physical and mechanical characteristics of soft soil in South Galesong, analyze and calculate the physical properties, mechanical properties including the shear strength of the soft soil. The method used in this research is an experimental research method. The research was carried out using a direct shear test to test the shear strength of soil from South Galesong and various soil mixtures with the addition of cement for stabilization. The mixture variations tested were 5%, 10%, 15%, 20% and 25% cement. The results of the research show that the soil from South Galesong has a moderate level of plasticity, has silty clay properties and is cohesive. The shear strength of the soil is 248.58 kPa. The largest increase in shear strength was obtained in a sample mixture of 90% soil + 10% cement with a curing time of 3 days with a shear strength of 322.03 kPa. When compared to the original soil with a shear strength of 248.58 kPa, there was an increase in the soil shear strength of 29.55% of the original soil shear strength.